Analysis of the Innovative Application of Virtual Reality Technology in Physical Training of Colleges. (May 2020) - Zhang, Xiaotong; Liu, Tian; Liu, Qian; Wang, Mingyuan; Wang, Mingjie; Tian, Yuzhi
Abstract: In order to realize the effectiveness and scientificity of college physical training, we can integrate modern technology into college physical training, and promote the intellectualization and standardization of college physical training. In view of many problems that need to be solved in college physical education training, this paper designs a physical education training virtual simulation system by combining the application advantages of computer virtual reality technology, introduces the system functions and overall framework in detail, designs the corresponding functional modules, and expounds the advantages of computer virtual reality technology in college physical education training in detail. The research results show that it is necessary to apply computer virtual reality technology in college physical training, which can effectively promote the development of college physical training teaching, and promote college students to strengthen physical training.